Approach to Determining the Science and Innovation Funding Impact on the Socio-Economic Development of the EU Countries and Ukraine - Ihor MATYUSHENKO; Valery REZNIKOV; OLGA TOFANIUK; ALONA ZINCHUK (Communications of International Proceedings, 2021)
The study reveals the approach to determining the impact of funding of science and innovation on the socio-economic development of the EU countries and Ukraine. The paper uses the Cobb-Douglas production function for analysis. The given factor model reveals the dependence of GDP on Government budget allocations for R&D and Global Innovation Index. The models also analyze the impact of each of the GII sub-indices on the socio-economic development of countries. The calculations were carried out for 28 EU countries and Ukraine for 2014-2020.
Keywords: Gross domestic product (GDP); Global Innovation Index (GII); Sub-index; Government budget allocations for research and development (R&D)